2005
DOI: 10.1002/cbic.200500064
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Sensing of TNT with a Genetically Engineered Pore

Abstract: Engineered versions of the transmembrane protein pore alpha-hemolysin (alphaHL) can be used as stochastic sensing elements for the identification and quantification of a wide variety of analytes at the single-molecule level. Until now, nitroaromatic analytes have eluded detection by this approach. We now report that binding sites for nitroaromatics can be built within the lumen of the alphaHL pore from simple rings of seven aromatic amino acid side chains (Phe, Tyr or Trp). By monitoring the ionic current that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
145
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 39 publications
(52 reference statements)
0
145
0
Order By: Relevance
“…We show that air-stable DIBs still allow for the robust electrical characterization of ion channels inserted in the lipid bilayer. Previously, it has been demonstrated that black lipid membranes or DIBs can be used for biosensing (46)(47)(48)(49)(50), light sensing (26), microscale biobatteries (26), electrical circuits (51,52), and engineering tissue-like material (53). However, these suspended lipid bilayers have always been confined to fluid reservoirs (25,45).…”
mentioning
confidence: 99%
“…We show that air-stable DIBs still allow for the robust electrical characterization of ion channels inserted in the lipid bilayer. Previously, it has been demonstrated that black lipid membranes or DIBs can be used for biosensing (46)(47)(48)(49)(50), light sensing (26), microscale biobatteries (26), electrical circuits (51,52), and engineering tissue-like material (53). However, these suspended lipid bilayers have always been confined to fluid reservoirs (25,45).…”
mentioning
confidence: 99%
“…The versatility and specificity of stochastic sensing have been enhanced by introducing sensing elements (analyte binding sites) into the αHL pore by protein engineering, chemical modification, or the use of adapter molecules (1,4,5). Through such approaches, the stochastic detection of ions (1,6), small molecules (1,7,8), reactive molecules (9,10), and proteinligand interactions has been achieved (1,(11)(12)(13)(14). The stochastic detection of proteins has also been achieved with functionalized solid-state nanopores (15).…”
mentioning
confidence: 99%
“…Such engineered pores can be useful components to build sensors of cell-signaling molecules. It was also reported that binding sites for nitro-aromatics could be built within the lumen of the αHL pore, enabling the sensing of explosives such as TNT [160].…”
Section: Modulation Of Pore Activity Sensing Of Organic Compounds Amentioning
confidence: 98%